miR‐493 by regulating of c‐Jun targets Wnt5a/PD‐L1‐inducing esophageal cancer cell development - Wei Bian; Yishuai Li; Haiyong Zhu; Shaolin Gao; Ren Niu; Chuan Wang; Hao Zhang; Xuebo Qin; Shujun Li (Thoracic Cancer, 2021)
Abstract Background Esophageal cancer is one of the most common cancers across the globe; the 5‐year survival of esophageal cancer patients is still low. MicroRNA (miRNA) dysregulation has been implicated in cancer development, and the miRNAs play a pivotal role in esophageal cancer pathogenesis. It is urgently needed to find out how miRNA dysregulation was involved in esophageal cancer (EC) development. Methods Through experiments in vivo and in vitro, we explored potential signaling pathways, miR‐493/Wnt5A/c‐JUN loop, in EC. Their mechanistic roles in EC cell proliferation, migration, and invasion were investigated through multiple validation steps in EC9706 and TE13 cell lines and EC specimens. Results Overexpression of miR‐493 attenuates esophageal cancer cell proliferation, migration, and invasion in vivo and in vitro. Moreover, miR‐493 downregulation is an unfavorable factor in EC and negatively correlated with Wnt5A. The existence of miR‐493 is also an important attribute of metabolism. Based on mechanism analyses, we show that miR‐493 inhibits the activity of c‐JUN and p‐PI3K/p‐AKT with enhanced p21 and directly regulates Wnt5A expression and function, whereas c‐JUN binds the promoter region of miR‐493 and suppressed the expression of miR‐493, forming a negative feedback loop. Conclusions The miR‐493/Wnt5A/c‐JUN loop is a molecular feedback loop that refers to the development of esophageal cancer cells and a potential target for the treatment of esophageal cancer.